Польські студенти Михайла Грушевського у Львівському Університеті: кількісна динаміка та дидактичні преференції - Telvak, Vitalii; Telvak, Viktoria; Radchenko, Oleh (Przegląd Wschodnioeuropejski, 2026)
The article reconstructs the student audience of M. Hrushevsky of Polish origin, namely, its quantitative parameters and didactic preferences. The study has revealed that the dean’s catalogs portray Hrushevsky as a sought-after professor for Polish youth, who, along with Jews, were the largest group among the scientist’s non-Ukrainian students. When choosing the historian’s courses, Polish students pursued the goal of deepening and diversifying their professional interests in the field of history and culture of lands that, in their ideas, were an integral part of the Polish-Lithuanian civilizational space. We have concluded that the knowledge acquired by Polish students at the lectures of Hrushevsky on deconstructing imperial narratives contributed to their rethinking of the past of their people. Communication with the professor also prompted them to understand the cultural and political demands of Ukrainians, which contributed to the establishment of an interethnic dialogue.